THE ACADEMIC PROFESSION AMONG FACULTY AT SAUDI UNIVERSITIES - Al Mohsen, Mohsen A (European Scientific Journal, ESJ, 2014)
Discourse about the academic profession on higher education institutions has grown in recent years. This paper explores the significant role of the academic profession. In addition, it gives an overview of the problems and challenges surrounding academic profession among Saudi faculty members. The study has included a proposal to improve the process of the academic profession, and to develop faculty performance for teaching, research process, and society services.